Sustainability's Meaning for Design - Samantha Barbolan; Michele Sinico (DIID, 2024)
The necessary dialogue between users, students, and professionals in the field of sustainable design requires a precise understanding of the conceptual meaning of the term “sustainability”. This concept is multi-componential, and different categories of actors in the design scene attribute varying components and varying weights to each component. This research, conducted on a sample of 304 participants, employed qualitative analysis to map the differences between the groups, both for the static definition of the concept and the definition anchored in perceptual data. Our research finds significant differences in conceptualization between the different groups: the idea of sustainability is substantially different between designers and users. The differences identified by this study are essential for designers who aim to create in a way that aligns with the categorization of users, in order to trigger an effective circular process.